Nursing Students’ Epistemological Beliefs and Critical Thinking Skills - Çobanoğlu, Asuman; Bilgiç, Şebnem (Makara Journal of Health Research, 2024)
Background: Epistemological beliefs and critical thinking affect the approach to knowledge and decision-making processes in nursing practice. These characteristics positively contribute to the personal development and quality of patient care of nurses. This study investigated the relationship between nursing students’ epistemological beliefs and critical thinking skills. Methods: This descriptive and correlational study included 752 students studying nursing. The study was conducted with students enrolled in nursing programs at two state universities located in the northeast and west of Turkey. Data were collected using a Student Information Form, the Epistemological Beliefs Questionnaire (EBQ), and the Critical Thinking Disposition Scale (CTDS). Results: The mean age of the students was 20.49 ± 1.73 years, and 78.2% were females. The students’ mean scores were 82.73 ± 12.05 on the total EBQ and 43.00 ± 5.35 on the CTDS. A negative and moderate (r = −0.315, p = 0.000) relationship was noted between the nursing students’ mean scores on the EBQ and CTDS. Conclusions: The study results indicate that the nursing students’ epistemological beliefs and critical thinking levels were above mean and that students with higher epistemological beliefs had higher critical thinking skills. According to these findings, utilizing instructional strategies incorporating practice and questioning in nursing education may enhance students’ epistemological beliefs and critical thinking abilities.